Interpreting the Efficiency of Investment Decisions from the Entrance of Accounting Profit Quality Estimation Models: (Application in a Sample of Industrial Companies and Banks Listed in the Iraq Stock Exchange) - عبدالله, بسام أحمد; عگيد, بيريفان عبدالخالق (Polytechnic Journal of Humanities and Social Sciences, 2023)
The research seeks to study the relationship between the Earning Quality Accounting and the Investment decisions Efficiency and the effects resulting from the relationship between them for a sample of companies listed in the Iraqi Stock Exchange because it is considered important in determining the Investment decisions Efficiency, as it sheds light on the need to pay attention to the quality of financial statements and reports and attention to actual profits Which are disclosed in the financial statements of companies, especially when making investment decisions. The research used descriptive analysis using the statistical program (Eviews 12) for the research variables, based on the quarterly financial statements extracted from the companies’ financial statements, and the research sample was chosen consisting of 20 companies (10 industrial companies and 10 banks), listed in the Iraq Stock Exchange according to criteria related to the provision of audited and continuous financial statements throughout the study period extending during (2018 - 2020), In order to test the research hypotheses, the researchers relied on five models to measure the quality of accounting profits (accounting conservatism, quality of receivables, estimated accruals, profit continuity, predictive ability) and testing the correlation between the independent variables and the dependent variable and an impact statement on the approved variable (Investment decisions Efficiency), where the results showed a significant relationship between the predictive ability and the quality of receivables with the Investment decisions Efficiency, while the rest of the variables appeared not moral, which means that the management of companies depends on information they own in particular and does not depend on the information published in the financial statements when making investment decisions, and The most outstanding suggestion is for investors to rely on other information related to the company other than the information that is disclosed in the financial statements because it can be manipulated These lists are made by corporate managers, especially if they are not of high quality because it helps increase the asymmetry of information between management and investors.